2009
DOI: 10.1016/j.mimet.2008.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Use of the frc gene as a molecular marker to characterize oxalate-oxidizing bacterial abundance and diversity structure in soil

Abstract: International audienceOxalate catabolism, which can have both medical and environmental implications, is performed by phylogenetically diverse bacteria. The formyl-CoA-transferase gene was chosen as a molecular marker of the oxalotrophic function. Degenerated primers were deduced from an alignment of frc gene sequences available in databases. The specificity of primers was tested on a variety of frc-containing and frc-lacking bacteria. The frc-primers were then used to develop PCR-DGGE and real-time SybrGreen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 58 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Moreover, molecular and genetic studies have revealed the presence of chitinolytic genes among important members of the Oxalobacteraceae (23,(51)(52)(53)60). Thus, the genus Streptomyces, along with Oxalicibacterium (in the presence of fungi), might play key roles in disease-suppressive soils as being part of the amendment-reactive microbiota (5,19,20,54). A further lead, obtained from chiAbased Roche 454 deep pyrosequencing analysis of the June-10 chitin-amended field and soil from a microcosm experiment (17,21), recently indicated an increase in the abundance of Oxalobacteraceae-like sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular and genetic studies have revealed the presence of chitinolytic genes among important members of the Oxalobacteraceae (23,(51)(52)(53)60). Thus, the genus Streptomyces, along with Oxalicibacterium (in the presence of fungi), might play key roles in disease-suppressive soils as being part of the amendment-reactive microbiota (5,19,20,54). A further lead, obtained from chiAbased Roche 454 deep pyrosequencing analysis of the June-10 chitin-amended field and soil from a microcosm experiment (17,21), recently indicated an increase in the abundance of Oxalobacteraceae-like sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxylates such as citrate and malate are a major source of carbon for rhizosphere bacteria, and malate has even been postulated to act as a signal to recruit beneficial microorganisms (Rudrappa et al, 2008). In contrast, using oxalate as carbon source, a phenotype referred to as “oxalotrophy,” is a rare trait of bacteria, although it occurs across a wide range of phylogenetically distant groups (Sahin, 2003; Khammar et al, 2009). In addition to citrate and malate, which are common components of root exudates, oxalate has also been shown to be a major root exudate of soil-grown plants (Dessureault-Rompre et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although oxalate is a rather "poor" substrate, a number of oxalotrophic bacteria have been isolated from various ecological niches, including terrestrial (10) and aquatic (64) habitats and the gastrointestinal tract, under both aerobic and anaerobic conditions. Phylogenetically, oxalotrophic bacteria belong to distinct groups (33,(55)(56)(57).…”
mentioning
confidence: 99%